Identifikasi Karakter Morfofisiologi Kedelai Adaptif Lahan Masam - Sudrajat, Denny (Politeknik Negeri Lampung., 2010)
Efforts to increase soybean production in acid soil can be done in two ways, were: (1) Calcification to improve the physical and chemical properties of land that is suitable for planting soybeans, or (2) through use of genotypes that have a high tolerance for stress Al (Muhidin,2002). Therefore, adaptive soybean varieties with the sour land 30-35% aluminum saturation and pH 4.5-5.0, and supported by soybean cooking genjah age (75 days) prospectively for soybean development outside Java. Varieties that have been known to land a sour adaptiv like Ratai, Sibayak, Nanti, Tanggamus and Seulawah consistent power adaptations to soil acidity, this is indicated by both agronomic traits and physiology. Anatomical characters show the most stress in response to Al is the root, the varieties sour adaftiv land rooting organ hampered not at all, the roots can develop well. The study concluded that the varieties that have been known to land a sour adaftiv like Ratai, Sibayak, Nanti, Tanggamus and Seulawah have a high consistency of the soil acidity, with roots showing growth and the number of normal pods. Root dry weight parameters can be used to assess the toxicity consideration Aluminum plant, which can be used as character selection in plant breeding process. Keywords: Morfofisiologi, Aluminium